TITANIUM MOBILITY IN METAMORPHIC SYSTEMS: A REVIEW - Van Baalen M.R. (My University, 1993)
Titanium is a dispersed lithophile element commonly regarded as chemically immobile at sub-magmatic temperatures. However, a growing number of field studies demonstrate that Ti is somewhat mobile in certain environments. This review examines the current state of knowledge concerning the mobility of Ti during alteration and metamorphism of crustal rocks. Also considered are relevant Ti-oxide solubility data from experiments and determinations of Ti concentrations in natural waters.Where Ti mobility is well documented, its length scale is ≤ 10 m. However, Ti may move greater distances in deep crustal shear zones. The solubility of Ti-oxides in geologic fluids is strongly temperature dependent. Under low- to medium-grade metamorphic conditions Ti mobility is limited by the low solubility of Ti-oxides in the associated fluids. Under eclogite conditions Ti mobility is probably limited not by Ti-oxide solubility (which reaches 1% [Ti]) but by restricted fluid flow in low-permeability rocks.